2015
DOI: 10.1142/s1088424615500546
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vitro photocytotoxicity of water-soluble dendritic pheophorbide-a

Abstract: Photosensitizers can produce highly reactive singlet oxygen with exposure to visible light and are used in photodynamic therapy to treat a variety of tumors. We report on the synthesis of triethylene glycol dendron-conjugated pheophorbide-a 5, a novel photosensitizer. The characteristic absorption bands (Soret and Q-bands, l max = 405 and 670 nm, respectively) of 5 were appeared clearly in aqueous solution, due to the improved water-solubility of the dendron moiety. The value of singlet oxygen quantum yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Other research groups have reported on pheophorbide and chlorin derivatives for efficient photosensitized eradication of tumor cells by alleviating solubility and aggregation problems. We and others have observed that polyethylene glycol (PEG) groups bonded to chlorophyll sensitizers can increase their solubility in solution, cell uptake, and phototoxicity in cancer cells. But previous work with chlorin e 6 had required chemically bonding each PEG group individually, with the third PEG adding in low yield (triPEG‐chlorin silica 2 and triPEG‐chlorin Teflon/PVA nanocomposite 3 , Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups have reported on pheophorbide and chlorin derivatives for efficient photosensitized eradication of tumor cells by alleviating solubility and aggregation problems. We and others have observed that polyethylene glycol (PEG) groups bonded to chlorophyll sensitizers can increase their solubility in solution, cell uptake, and phototoxicity in cancer cells. But previous work with chlorin e 6 had required chemically bonding each PEG group individually, with the third PEG adding in low yield (triPEG‐chlorin silica 2 and triPEG‐chlorin Teflon/PVA nanocomposite 3 , Figure ).…”
Section: Introductionmentioning
confidence: 99%